New potential biomarkers of Alzheimer's disease: markers of endothelial dysfunction and neuroinflammation. - A. K. Minochkin; V. Yu. Lobzin; N. N. Suchentseva; O. S. Popov; S. V. Apalko; S. G. Sherbak (Неврология, нейропсихиатрия, психосоматика, 2022)
Alzheimer's disease (AD) is the most common cause of dementia in the elderly. The aim of the work wasObjective: to determine the relationship between laboratory biomarkers in blood plasma and cerebrospinal fluid (CSF) in patients with AD and indicators of neuropsychological testing.Patients and methods. 52 patients with AD were examined, in which the concentration of 90 potential biomarkers were measured in blood plasma and CSF. Neuropsychological assessment included the Mini-Mental State Exam (MMSE), Frontal Assessment Battery (FAB), Montreal Cognitive Assessment (MoCA), and etc.Results and discussion. Correlations of different strength between the values of biomarkers in blood plasma and CSF and the results of neuropsychological assessment were revealed. A correlation was found between the soluble cell adhesion molecule (sICAM-1) in blood plasma and the largest number of neuropsychological tests sensitive to dementia stages (MoCA, MMSE, FAB) in patients with AD at the dementia stage. A correlation was found between the concentration of growth/differentiation factor 15 and interferon γ in blood plasma and FAB scores in patients with AD. The levels of granulocyte colony-stimulating factor (G-CSF) in CSF were associated with the dementia stage in AD, and the interleukin-1 receptor antagonist (IL-1RA) levels, on the contrary, with stages preceding the development of dementia in AD.Conclusion. sICAM-1 level in blood plasma, which is a marker of endothelial dysfunction, may be an indicator of the severity of the vascular neurodegenerative process in AD at the dementia stage. G-CSF in the CSF is associated with the dementia stage in AD, and IL-1RA – with the pre-dementia stage of AD, which determines the prospect of their further study as diagnostic markers.